Perencanaan Tata Letak Gudang dengan Prinsip 5S (Seiri, Seiso, Seiton, Seiketsu, dan Shitsuke) Pada PT. Aneka Coffee Industry Guna Meminimalkan Waktu Pencarian di Gudang - Setiana, Aldiansyah Fiqri; Murnawan, Hery (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
PT. Aneka Coffee Industry is an industrial company in Indonesia engaged in the production of coffee, both in the form of beans and processed coffee products. This research aims to plan warehouse layout using the 5S principles (Seiri, Seiso, Seiton, Seiketsu, and Shitsuke) at PT. Aneka Coffee Industry with the goal of minimizing search time in the warehouse. The method used in this research includes collecting primary and secondary data related to storage and retrieval processes in the warehouse and applying the 5S principles. Analysis was conducted to evaluate the effectiveness of the 5S principles in reducing search time in the warehouse. The results of the research indicate that the application of the 5S principles can improve warehouse layout efficiency and significantly reduce search time. The implication of this research is the importance of implementing the 5S principles in warehouse layout planning to enhance company productivity and operational efficiency. In conclusion, integrating the 5S principles becomes one of the effective strategies in enhancing warehouse performance and reducing search time for items.